2014
DOI: 10.1093/hmg/ddu116
|View full text |Cite
|
Sign up to set email alerts
|

Genetic suppression of β2-adrenergic receptors ameliorates tau pathology in a mouse model of tauopathies

Abstract: Accumulation of the microtubule-binding protein tau is a key event in several neurodegenerative disorders referred to as tauopathies, which include Alzheimer's disease, frontotemporal lobar degeneration, Pick's disease, progressive supranuclear palsy and corticobasal degeneration. Thus, understanding the molecular pathways leading to tau accumulation will have a major impact across multiple neurodegenerative disorders. To elucidate the pathways involved in tau pathology, we removed the gene encoding the beta-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…It is also plausible that the increase in tau pathology in the ICI-treated mice is due to a direct interaction between β2ARs signaling and tau. Toward this end, we recently showed that genetically reducing β2AR signaling significantly decreased tau pathology in the presence and absence of Aβ (Wang, et al, 2013; Wisely, et al, 2014). While these genetic data could appear counterintuitive with the data presented here, there are several mechanisms that could explain the variation between genetic and pharmacological data.…”
Section: Discussionmentioning
confidence: 99%
“…It is also plausible that the increase in tau pathology in the ICI-treated mice is due to a direct interaction between β2ARs signaling and tau. Toward this end, we recently showed that genetically reducing β2AR signaling significantly decreased tau pathology in the presence and absence of Aβ (Wang, et al, 2013; Wisely, et al, 2014). While these genetic data could appear counterintuitive with the data presented here, there are several mechanisms that could explain the variation between genetic and pharmacological data.…”
Section: Discussionmentioning
confidence: 99%
“…A has been shown to interact with  adrenergic receptors which regulate gene expression and the activity of receptors including AMPA-type glutamate receptors via the cAMP/PKA signaling cascade. 64,65 Phosphorylation of AMPA receptor GluA1 subunits by PKA has been shown to increase channel opening probability which results in augmented calcium entry into the cell, leading to neurotoxicity. 66 A study 67 has shown that the addition of Aβ to neuronal cultures causes neurotoxicity by strengthening calcium-dependent AMPA-receptor generated currents.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…Given that the change of expression levels of GPCRs would have an effect on the related biological processes, these observations suggested a potential role of GPCR in the pathological progression of AD, which requires further investigation (Blalock et al, 2004 ). Until now, numerous promising works have been done to connect GPCRs and AD pathology based on three hypotheses: the Cholinergic hypothesis, the Tau hypothesis and the Amyloid hypothesis (Thathiah and De Strooper, 2009 , 2011 ; Wisely et al, 2014 ).…”
Section: Gpcrs and Admentioning
confidence: 99%
“…Numerous studies have presented evidence that implicate GPCRs in the pathogenesis of Alzheimer’s disease (AD) and in multiple stages of the hydrolytic processing of amyloid protein precursor (APP), a precursor protein involved in the formation of amyloid plaques found in AD patients’ brain (Thathiah and De Strooper, 2009 , 2011 ; Wisely et al, 2014 ). Indeed accumulated data have shown that GPCRs can bind to β-secretase (β-site APP cleaving enzyme 1, BACE1) and γ-secretase which are key enzymes in the hydrolytic processing of APP (Liu et al, 2013 ; Nelson and Sheng, 2013 ; Thathiah et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%